AN ANALYSIS OF TAYMIYYAH’S PERSPECTIVE ON GOVERNMENT REGULATION AFFORDABILITY IN INDONESIA - Ali Musa Harahap (Politik Indonesia: Indonesian Political Science Review, 2025)
One of the primary roles of the government is to regulate the private sector. Concerns regarding housing affordability are widespread among low- and middle-income households across both urban and rural areas in Indonesia, with many struggling to purchase a ome. This paper aims to highlight the issue of housing affordability and to examine the concept of government regulation from the perspective of Ibnu Taymiyyah. The theoretical foundation is based on Ibnu Taymiyyah’s value-based concept of price regulation. A qualitative method is employed, using a descriptive philosophical analysis of Ibnu Taymiyyah's thought, accompanied by interpretation of relevant texts, and contextualized within Indonesia's housing market. The purpose of this study is to emphasize the importance of government regulation as a just and proper system to prevent arbitrary practices by private actors. Government regulation, in this context, plays a critical role in supporting democratic development in Indonesia. Its implementation implies that price regulation is a necessary measure to ensure the welfare of the Indonesian state.